The book of Genesis: composition, reception, and interpretation - Evans, Craig A.; Lohr, Joel N.; Petersen, David L. (Vetus Testamentum / Supplements, 2012)
Written by leading experts in the field, The Book of Genesis: Composition, Reception, and Interpretation offers a wide-ranging treatment of the main aspects of Genesis study. Its twenty-nine essays fall under four main sections. The first section contains studies of a more general nature, including the history of Genesis in critical study, Genesis in literary and historical study, as well as the function of Genesis in the Pentateuch. The second section contains commentary on or interpretation of specific passages (or sections) of Genesis, as well as essays on its formation, genres, and themes.. read more
Includes bibliographical references and index
Keywords: Bible -- Genesis -- Criticism, interpretation, etc; Bibel -- Genesis; Aufsatzsammlung; Rezeption; Bibel / Altes Testament; Komposition; Bibel / Genesis